If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (14x + 8) = (-12x + 3) Reorder the terms: (8 + 14x) = (-12x + 3) Remove parenthesis around (8 + 14x) 8 + 14x = (-12x + 3) Reorder the terms: 8 + 14x = (3 + -12x) Remove parenthesis around (3 + -12x) 8 + 14x = 3 + -12x Solving 8 + 14x = 3 + -12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12x' to each side of the equation. 8 + 14x + 12x = 3 + -12x + 12x Combine like terms: 14x + 12x = 26x 8 + 26x = 3 + -12x + 12x Combine like terms: -12x + 12x = 0 8 + 26x = 3 + 0 8 + 26x = 3 Add '-8' to each side of the equation. 8 + -8 + 26x = 3 + -8 Combine like terms: 8 + -8 = 0 0 + 26x = 3 + -8 26x = 3 + -8 Combine like terms: 3 + -8 = -5 26x = -5 Divide each side by '26'. x = -0.1923076923 Simplifying x = -0.1923076923
| 10=2+3x+4-2x+2 | | x-2-2=2 | | 2-12n=0 | | -8.5c+5.5c=25.5 | | w=my+b | | 2x(-3)= | | 341/6=x+61/4+123/8 | | 2.1x=51.24 | | -116=-4(n-9)-12(1-12n) | | 45+4x+3x+6x=180 | | -20=2n+-9 | | 1-6=-5 | | 6r-3-2r-4=1 | | -20x=221+6x | | 5-8x+3x^2= | | -20=2+-9 | | 8=0.2x | | 13x+52=85 | | 3p*6-7q+14p*6= | | 12-12x^2=0 | | x+3+4x-58= | | 0=2(x+2)+4(1+2x) | | 6-4b=14 | | X+X/2-4=X/4 | | 5x+(x-4)=76 | | -11=r+1+4r+3 | | 6x-14=5x | | 4c-5(x-2)=9x+14 | | 5+16f=2(8f+2.5) | | 5(2z+11)=3z+103-z | | X^2+5x+64=0 | | 5n-3=2n+4 |